ANALYSIS OF HOSPITAL MANAGEMENT INFORMATION SYSTEM (SIMRS) AND ITS RELATION TO THE READINESS OF ELECTRONIC MEDICAL RECORD (RME) IMPLEMENTATION IN RSUP. SANGLAH DENPASAR - I PUTU AGUS YOGA PERMANA; Gusti Ayu Eka Sutrisnawati; Ni Ketut Juniati (Syntax Corporation Indonesia, 2023)
A hospital is a health service institution that provides plenary individual health services that provide inpatient, outpatient, and emergency services. This study focuses on the implementation of SIMRS using PIECES analysis where researchers assess SIMRS using six aspects, namely performance, information, economy, control, efficiency and service. Where the results of this system analysis aim to ascertain whether the system created has no error functions or the system is running properly. The method used in this analysis is the PIECES framework which includes 6 aspects of reference, namely: Performance, Information and data, Economics, Control and Security, Efficiency, and Service. This method is applied to calculate the level of user satisfaction with the system which later the results are used for evaluation of the system related to the development of system quality. Performance according to performance calculations in the PIECES analysis obtained a value of 3.96 with the predicate Satisfied, but there are several things that must be improved.